LINGKUNGAN KOTA LAYAK ANAK (CHILD-FRIENDLY CITY) BERDASARKAN PERSEPSI ORANGTUA DI KOTA YOGYAKARTA - Widiyanto, Dodi; Rijanta, R. (Bumi Lestari; Vol 12 No 2 (2012), 2012)
The research aims at identifying the concepts related to child-friendly city as perceived by parents in Yogyakarta municipality. A structured questionnaire is employed to collect the data on the ideal urban environment of a child-friendly city as perceived by the respondents. The respondents are widthdrawn from four spots of locations in the city used as child playgrounds, i.e: Sultan Palace Yard, Taman Pintar (Smart Garden), Gembira Loka Zoo and Open Space under the flyover of Lempuyangan Station. Concepts related to child-friendly city are explored and grouped through a factor analysis. From the process of factor analysis, four measures of ideal urban environment related to child-friendly city can be identified. They are policy, protection, environment and planning for children. The first three concepts are well suited with the Indonesian national policy on child-friendly city. Whereas the last concept, planning for children, needs special  attention as a part of the existing concept of policy, or it should be an independent concept that needs to be accomodated in planning norms, standards, procedures and manuals in an urban environment.
Keywords: urban environment, child-friendly city, perception, urban planning, Yogyakarta